Perencanaan Sistem Persediaan Bahan Baku Industri Garmen di PT. DM - Nunung Nurhasanah; Syarif Hidayat; Ajeng Putri Listianingsih; Devi Utami Agustini; Faikar Zakky Haidar; Nida'ul Hasanati (Jurnal Optimasi Sistem Industri, 2014)
One of the effort to presence with global competition in the era of the Asean Economic Community (AEC) in 2015, making it the various parties, both government, private, and Small and Medium Industries (SMEs) to compete with products made in ASEAN countries. One of the things that can be done is to make the efficiency of the production costs. For that, we need a production planning and control are very closely related to the raw material. The presence of raw materials becomes important because if there is a shortage of raw materials, will inhibit the production process. If the stock overload can make an effect on the cost savings that can increase the cost of the company. IKM DM is one of the industry that concerned to the manufacture of clothing garment, especially to the shorts. The Problems that are often faced by SMEs is the frequent occurrence both in the warehouse overstock raw materials and finished goods warehouse. It is necessary for research in determining the amount of raw materials in the warehouse, so that capital is not held long. This study only focus to three kinds of pants that has all size model, big size type, and type pants buckle. The purpose of this study is predicting the number of requests using the ARIMA period of 3 months in April, May, and June 2014; planned economic order quantity and raw material ordering schedule using the EOQ method. The study also discusses the raw materials inventory system either periodically or in a perpetual; and ends with the calculation of the limitations of the warehouse. Forecasting pants all size in April, May and June respectively 30 840, 31 962, and 32 357 pieces; the big size pants are 8.645,8.782, and 8782; and the buckle pants are 4,960, 4,980, and 4,980 pieces. As for the number of ordering raw materials at economical polly cloth pants all size, buckle, and the big size of 45 562-yard; 17 684; and 25 534 yards. As for the scheduling of raw materials in the all size type, big size type, and the buckles have ROP values of 4.470,1.382, and 660 yards. The frequency ordering as many as 6 times, 3 times, and 2 times with intervals of 30 days, 64 days, and 80 days. From the calculation of the inventory system, obtained perpetual method has the smallest cost. For the calculation of the limitations vast storehouse of raw materials needed 4 shelves for storage of accessories with a total area of 107m2, with a total of 144m2 warehouse area.